Estratégias de inovação sob a perspectiva da Resource- Based-View: análise e evidências em empresas de base tecnológica - Sanches, Paula Luciana Bruschi (2011)
This dissertation has as a main objective to analyse the innovation strategies of technologybased companies, under the Resource-Based View perspective. To this, it was adopted as a methodological procedure a qualitative approach by using the multiple case study method in four technology-based companies located in the northeastern part of Brazil. To the data analysis, it was elaborated two scripts of semi-structured interviews which were answered by the companies directors and two software specialists that totalized six interviewed. In the data analysis, it was used a process of continuous analysis, recurrent, demonstrating, thus, a multidirectional cycle with the help of Atlas.ti software. On the first level, the data was analysed in conformity with their characteristics and their individual contexts (within case). Afterwards, on the second level, a broaden scenario was involved in which the results in the cases were crossed and compared among them (cross case). Then, four categories guided the analysis: the factors that motivated the innovation, the types of innovation strategies, the resources and capacities explored by the innovation strategies and the resources and capacities under the optics of the VRIO model. The obtained results allowed the specific objectives to identify the strategies of innovation realized by the companies and the resources and capacities explored by them. In the studied companies, innovations occure in a routine context since that changing constantly is a part of needed activities to survive in a market. Among the factors that drive innovation, it is emphasized that these can be grouped into broader dimensions, such as customers, continuous development, environment, market, people and external resources. Even though similar factors in their name, companies use them for different purposes in their innovations and what is important for one may not necessarily be to another. As for innovation strategies, it was found that the four cases have a reactive approach to changing environments, performing mostly exploitative innovation strategies through incremental innovations and open. In this sense, it was possible to identify fifteen different types of innovation strategies, which in turn are based on various features and capabilities for its realization. Among them, we present the know-how, the design of organizational structure, organizational culture, the way projects are done and investments in R & D. With regard to resources and capabilities that were shown to have potential to provide sustainable competitive advantage for companies in the light of the VRIO model, intangible resources stand out, such as know-how, organizational culture, entrepreneurship and innovation, responsiveness, the way projects are done, partnerships with other institutions, as well as the relationship between employees. It is concluded that although it was possible to identify the features and capabilities of companies, respondents do not know how to point them easily, and therefore do not realize the cause of its advantages. The changes required both technologically and strategically reinforce the value of the perspective of RBV in the selection, acquisition or improvement of tangible and intangible resources of technologybased companies.